Teater Garasi Seni Rupa Media Naratif Peristiwa Teater â€œWaktu Batuâ€ - Afrianto, Damar Tri (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2014)
Garasi TheaterÂ  has a visual awareness and fine art aspect as their language. It seems when Garasi theaterÂ  creates visual works from Javanese mythology â€œSudamala, Murwakala, Watugunung and the end history of Majapahit as a groundwork. Garasiâ€™s tracking about Javanese mythology and the history of Majapahit in â€œWaktu Batuâ€ as if looking for cultural and spiritual identity answer of space and time disorientation. The presence of visuality should be able to create new narratio of mythology and history. Art instalation, contemporary sculptures, mix media art and art video are trying to dialogue with another element of theater on stage. Based on creative process and architectural performance can be seen that Teater Garasi are creating a theater which is dominated by visual images.The visuality of Garasi Theater in â€œWaktu Batuâ€ try to incorporating Javanese ancient spirituality roots through its mythology and history, and still using the lastest contemporary art.Keyword: Art Visual Performance, Garasi Theatre, Waktu Batu Story.